Non-LTE Abundances of Sodium in the Atmospheres of Red Giants of the Thick and Thin Galactic Disks. Issue Volume 9:Issue S298(2013) (6th January 2014) - Alexeeva, Sofya; Pakhomov, Yury; Mashonkina, Lyudmila
Abstract: We determined NLTE abundances of Na in the atmospheres of 80 red giants including the 33 stars of the thin disk, 35 stars of the thick disk and 12 stars of Hercules stream.